Melt Spin Coating for X‐Ray‐Sensitive Hybrid Organic–Inorganic Layers of Small Carbazolyl‐Containing Molecules Blended with Tungsten. Issue 23 (21st October 2019) - Dobužinskas, Rokas; Poškus, Andrius; Viliūnas, Mindaugas; Jankauskas, Vygintas; Daškevičienė, Marytė; Getautis, Vytautas; Arlauskas, Kęstutis
Abstract : For the first time, a blend of carbazolyl‐containing small molecules and tungsten particles for X‐ray‐sensitive layers is developed using the solvent‐free melt spin‐coating (MSC) method. The composite films fabricated on a glass substrate, using aluminum as electrodes, are applied for direct current conversion of X‐rays with high signal‐to‐noise ratio, reliable on–off switching characteristics, and short‐ and long‐term stability. To elucidate the processes of charge carrier generation by X‐rays, Monte Carlo simulations of X‐ray‐induced current are performed. The response and charge transfer processes investigated by an X‐ray pulse experiment indicate possibilities for real‐time detection. Abstract : A blend of carbazolyl‐containing small molecules and tungsten particles for X‐ray sensitive layers is developed for the first time using solvent‐free coating (MSC) method. The layers are applied for direct current conversion of X‐rays with high signal‐to‐noise ratio, reliable on‐off switching characteristics, short‐ and long‐term stability. The results of these investigations show possibilities for real‐time detection.